Pelatihan Platform Digital Untuk Optimalisasi Shoft Skill Dan Hard Skill Gen Z - Adam Pratama; Nugroho, Ariyanto; Eka Amalia; Nugroho, Rizki Dwi (Jurnal Abdimas Tri Dharma Manajemen, 2025)
Generation Z faces great challenges in entering the increasingly competitive world of work. Digital platform-based training is one of the solutions to improve their competence, both in soft skills such as communication, teamwork, and leadership, as well as hard skills such as programming, data analysis, and graphic design. This activity aims to provide interactive training designed according to the needs of Gen Z, with a technology-based and collaborative approach. The program uses hands-on training methods, online tutorials, and case-based simulations. The results of the training showed an increase in participants' understanding and skills in using digital platforms to develop themselves professionally. Keywords: Generation Z, Soft Skill, Hard Skill, Digital Platformplatforms to develop themselves professionally.